A cobertura da mídia brasileira sobre o Golpe Militar de 15 de Julho de 2016 na Turquia - Elemen, Yusuf (2018)
On July 15, 2016, there was a military coup attempt in Turkey by a faction within the Turkish Armed Forces that presented themselves as the "Council of Peace at Home", but, this time - different from what happened with the previous ones, such as 1960, 1971, 1980 and 1997 coup d'état - was not successful. The attempted coup is considered the most important event since 1946 by its political and social results. In this sense, the Brazilian press published a great volume of news on the subject, due to the international impact generated by the coup. The aim of this work is to analyze the coverage of the newspaper Folha de S. Paulo, O Estado de S. Paulo and O Globo, from July 16 to August 30, 2016